2013
DOI: 10.1115/1.4025929
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Smoke Reduction Effect of Post Injection in Combination With Pilot Injection for a Diesel Engine

Abstract: With the universal utilization of the common-rail injection system in automotive diesel engines, the multistage injection strategies have become typical approaches to satisfy the increasingly stringent emission regulations, and especially the post injection has received considerable attention as an effective way for reducing the smoke emissions. Normally the post injection is applied in combination with the pilot injection to restrain the NOê missions, smoke emissions, and combustion noise simultaneously, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The total injection quantity was set at 33 mm 3 /cycle, where the IMEP was approximately 1.0 MPa. On the basis of the previous study [14], the pilot injection quantity was set at 6 mm 3 /cycle to realize the entirely mixing-controlled combustion of the main spray and a relatively high smoke level for easy detection of the soot-reduction effect of post injection. The intake manifold pressure and temperature were adjusted to 120 kPa and 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…The total injection quantity was set at 33 mm 3 /cycle, where the IMEP was approximately 1.0 MPa. On the basis of the previous study [14], the pilot injection quantity was set at 6 mm 3 /cycle to realize the entirely mixing-controlled combustion of the main spray and a relatively high smoke level for easy detection of the soot-reduction effect of post injection. The intake manifold pressure and temperature were adjusted to 120 kPa and 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…Each subswarm searches a small section of the design space using the best results from other subswarms only changing its assigned variables. If any subswarm SN improves its best solution (G best ), this is communicated to other subswarms using a context vector (X context ) given by equation (7). The fitness of the context vector can only improve with each algorithm iteration, which can lead to the algorithm getting stuck in local minimums without the ability to climb out and move to better spaces in the design space.…”
Section: Optimization Methodologymentioning
confidence: 99%
“…6 Careful control of the pilot quantity is needed as large pilots can take increasing amounts of oxygen away from the main injection. 7 Additional pilots can be added to the compression stroke to promote premixing, but the increased heat of vaporization of diesel fuel can make it challenging to prevent wall wetting. 5 Small post injections increase the burning rate of the main injection fuel when timed near to the main injection.…”
Section: Introductionmentioning
confidence: 99%
“…In a heavy-duty diesel engine, the effects of injection strategies on emissions were investigated by many researchers, [3][4][5][6][7][8][9][10][11] it was found that small post injection mass with a short main-post injection interval produces less smoke; 6 dramatic soot reduction without a NO x penalty can be achieved by injecting enough fuel in post injection at an appropriate EGR rate; 8 there is a tradeoff relation between carbon monoxide (CO), hydrocarbon (HC), and NO x emissions with crank angle intervals increasing, lowest particulate matter emissions appear at middle post injection timing; 9 proper post injection may help in soot oxidation; 10 more CO formation and less HC emission are obtained during multiple injection combustion process, and simultaneous reductions of 58.7% and 25%, respectively, for NO x and soot can be achieved. 11 A new concept of variable injection pressure of multiple injections was proposed by Poorghasemi et al, 12 and it was found that increasing post injection pressure can reduce the soot emission significantly while the NO emission is in control.…”
Section: Introductionmentioning
confidence: 99%